Bar Instability and Formation Timescale across Toomre’s Q Parameter and Central Mass Concentration: Slow Bar Formation or True Stability - T. Worrakitpoonpon (The Astrophysical Journal)
We investigate the bar formation process using N -body simulations across the Toomre’s parameter Q ${}_{{\rm{\min }}}$ and central mass concentration (CMC), focusing principally on the formation timescale. Of importance is that, as suggested by cosmological simulations, disk galaxies have a limited time of ~8 Gyr in the Universe’s timeline to evolve secularly, starting when they became physically and kinematically steady to prompt the bar instability. By incorporating this time limit, bar-unstable disks are further subdivided into those that establish a bar before and after that time, namely, the normal and the slowly bar-forming disks. Simulations demonstrate that evolutions of bar strengths and configurations of the slowly bar-forming and the bar-stable cases are nearly indistinguishable prior to 8 Gyr, albeit dynamically distinct, while differences can be noticed afterward. Differentiating them before 8 Gyr is possible by identifying the proto-bar, a signature of bar development visible in kinematical maps such as the Fourier spectrogram and the angular velocity field, which emerges in the former group 1–2 Gyr before the fully developed bar, whereas it is absent in the latter group until 8 Gyr and such bar-stable disk remains unbarred until at least 10 Gyr. In addition, we find complicated interplays between Q ${}_{{\rm{\min }}}$ and CMC in regulating the bar formation. First, disk stabilization requires both high Q ${}_{{\rm{\min }}}$ and CMC. Either high Q ${}_{{\rm{\min }}}$ or high CMC only results in slow bar formation. Second, some hot disks can form a bar more rapidly than the colder ones in a specific range of Q ${}_{{\rm{\min }}}$ and CMC.